Innovated enhancing group efficiency of students of the Business Administration sector in credit training mode - Hop, Duong Van; Phuc, Vu Truc; Tu, Lê Thi Cam (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2021)
Through the survey, learn we found that research on group activities has several of works. However, there are still many problems to improve the scientific basis of solutions to improve the group performance of students in universities in general and the Business Administration in particular deep analysis and research is needed. In Vietnam, the passive learning style from high school directly affects students entering university. This creats passivity in students. Therefore, we need to analyze the main causes to find effective and practical solutions, both in terms of awareness and organizational skills, to conduct effective group learning. Teamwork skills are an important skill for success.